IMPLEMENTASI PENDIDIKAN INKLUSI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Rusdiyanto Rusdiyanto (Universitas Muhammadiyah Jember, 2018)
In Indonesia, the first Education for children with disabilities is called “Extraordinary School” (SLB). This study concerned the so-called ‘inclusive education’. The results of this study showed that (1) Junior High School Muhammadiyah 2 Malang used two models of the curriculum, namely, modified curriculum and adjusted curriculum, (2) learning patterns of children with special needs on Islamic Education subjects in Junior High School Muhammadiyah 2 Malang implemened 3 learning patterns. Among them were (i) learning together without any assistance from those who had high capability were taught by the subject teachers, (ii) learning together with assistances by a specially trained teacher (GPK) in addition to being taught by the subject matter teacher, and (iii) individual learning which was taught directly by GPK. Finally, with regard to evaluation, the results of the study showed that the evaluation system of children with special needs on the subject of Islamic Education in Junior High School Muhammadiyah 2 Malang emphasized two aspects which were the academic and non-academic Keywords : disabilities, extraordinary School.